Analysis of the Lead on Lip Tint Cosmetics on the Market Using UV-Vis Spectrophotometry Method - Gatut Ari Wardani; Siti Laila Abiya; Fajar Setiawan (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2020)
Analysis of the lead on lip tint cosmetics on the market has been successfully carried out. Before conducting the lead analysis, the method is first validated using the standard addition and measured by UV-Vis spectrophotometry. The validation of the lead content analysis method in lip tint using the UV-Vis spectrophotometry method was stated to meet the validity requirements. The validity parameters include linearity test (correlation coefficient = 0.9916), limit of detection (0.17 ppm), limit of quantitation (0.57 ppm), accuracy test (% recovery for a concentration of 4 ppm = 97.5%, 8 ppm = 93.8%, and 14 ppm = 98.6%), and precision (< 2% for all concentrations). Imported lip tint samples circulating in the market area of the Tasikmalaya city contain lead with a concentration of 2.149 ppm, so it is still declared safe for use by the public.